Basal Ganglia Compensatory White Matter Changes on DTI in Alzheimer's Disease - Wurst, Zdeněk; Birčák Kuchtová, Barbora; Křemen, Jan; Lahutsina, Anastasiya; Ibrahim, Ibrahim; Tintěra, Jaroslav; Bartoš, Aleš; Brabec, Marek; Rai, Tanya; Zach, Petr; Musil, Vladimír; Olympiou, Nicoletta; et al. (Cells, 2023)
The volume reduction of the gray matter structures in patients with Alzheimer's disease is often accompanied by an asymmetric increase in the number of white matter fibers located close to these structures. The present study aims to investigate the white matter structure changes in the motor basal ganglia in Alzheimer's disease patients compared to healthy controls using diffusion tensor imaging. The amounts of tracts, tract length, tract volume, quantitative anisotropy, and general fractional anisotropy were measured in ten patients with Alzheimer's disease and ten healthy controls. A significant decrease in the number of tracts and general fractional anisotropy was found in patients with Alzheimer's disease compared to controls in the right caudate nucleus, while an increase was found in the left and the right putamen. Further, a significant decrease in the structural volume of the left and the right putamen was observed. An increase in the white matter diffusion tensor imaging parameters in patients with Alzheimer's disease was observed only in the putamen bilaterally. The right caudate showed a decrease in both the diffusion tensor imaging parameters and the volume in Alzheimer's disease patients. The right pallidum showed an increase in the diffusion tensor imaging parameters but a decrease in volume in Alzheimer's disease patients.
Keywords: bílá hmota; Putamen; Alzheimerova nemoc; Alzheimer Disease; putamen; White Matter; lidé; zobrazování difuzních tenzorů; šedá hmota; Diffusion Tensor Imaging; Gray Matter; Humans